2018
DOI: 10.31575/jp.v2i3.106
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Partisipasi Anggaran, Informasi Asimetris Dan Budget Emphasis Terhadap Slack Anggaran

Abstract: Budget slack is a behavior of individuals and organizations in preparing budgets even more so if the budget is used as a basis for performance measurement. The occurrence of a budget slack, namely budgetary slack will make the performance look better in the eyes of superiors if they can achieve the budget goals. Budgetary slacks are often used to overcome uncertainties predicting the future and the allocation of resources will be carried out based on the projected budget costs, so that slack makes flexible. Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
0
1
6
Order By: Relevance
“…The results of this study are not in line with research conducted by (Meirina & Afdalludin, 2018). Meirina & Afdalludin (2018) found that information asymmetry has a significant positive effect on budgetary slack. And it means that if the information asymmetry increases, the budgetary slack will also increase, and vice versa.…”
Section: Effect Of Information Asymmetry On Budgetary Slack In Generacontrasting
confidence: 99%
“…The results of this study are not in line with research conducted by (Meirina & Afdalludin, 2018). Meirina & Afdalludin (2018) found that information asymmetry has a significant positive effect on budgetary slack. And it means that if the information asymmetry increases, the budgetary slack will also increase, and vice versa.…”
Section: Effect Of Information Asymmetry On Budgetary Slack In Generacontrasting
confidence: 99%
“…The results of this study are reinforced by Dunk's opinion in (Putranto, 2012) which states good government governance, namely as a situation that occurs if the governance applied becomes its responsibility better so that the working mechanism will be better and there is supervision from the leadership and the community. The results of this study are in line with research conducted by (MELASARI & NISA, 2020) and (Meirina & Afdaluddin, 2018). The effectiveness of Internal Control and the Implementation of Governance have a simultaneous effect on the Performance of Regional Heads The results of the third hypothesis (H3) test showed that the effectiveness of internal control, the governance of the government simultaneously affects the performance of regional heads.…”
Section: The Effect Of Governance On the Performance Of Regional Headssupporting
confidence: 89%
“…Hasil penelitian ini menunjukkan bahwa asimetri informasi memiliki pengaruh pada penciptaan budgetary slack serta bawahan yang ada pada kondisi asimetri informasi yang tinggi akan memiliki kecenderungan lebih tinggi dalam menciptakan budgetary slack dibandingkan bawahan dalam kondisi asimetri informasi rendah. Hipotesis pertama penelitian ini diterima dan hasil penelitian ini sejalan dengan hasil penelitian oleh Fanani dan Saudale (2018); Putra (2020); Savitri dan Sawitri (2014); serta Meirina dan Afdalludin (2018).…”
Section: Pengaruh Asimetri Informasi Terhadap Budgetary Slackunclassified